Implementasi Fuzzy Mamdani Untuk Menentukan Omset Bidang Usaha Koperasi Mahasiswa - Fitriyah Fitriyah; Prasanti Mia Purnama; Lifatin Nada; Alfin Fuji Hidayati (G-Tech: Jurnal Teknologi Terapan, 2024)
Student cooperatives (kopma) are cooperatives whose members are students from a particular university. In relation to the flow of funds in and funds out of kopma, the decision support system is a crucial tool for analyzing calculations of insufficient or excess funds.“This can minimize potential losses that arise as a result of inaccurate calculations of the flow of funds that have been collected. One effort to generate a decision support system is a fuzzy logic approach. This research aims to build a system that can determine cooperative turnover well using the fuzzy mamdani method.”“In this research, defuzzification was carried out using the centroid method with the help of MATLAB fuzzy toolbox r2016a software.””From the results of research that has been carried out by entering monthly income variables from January to December”in each sector, namely rental, photocopying and mini markets, it will produce turnover decision outputs of profit, break even and loss. Uses fuzzy mamdani to get output and has a membership function.”